A low cost omnidirectional high gain active integrated antenna for WLAN applications - Tan, Eng Leong (2013)
This work presents a low cost omnidirectional high gain active integrated antenna (AIA) for wireless local area network (WLAN) receiving system. The overall gain of the AIA is analyzed. Then, a planar monopole and an amplifier with single transistor is fabricated on low cost printable circuit board (PCB). By integrating them, simulation shows the AIA can achieve a relatively high gain at 2.4GHz.